EFFECT OF CRYOPRESERVED PLACENTAL EXPLANTS ON THE OVARY RESTORATION AFTER TORSION TREATMENT - Prokopiuk, V.Yu.; Lоginova, O.O.; Prokopiuk, O.; Somova, E. (World of Medicine and Biology, 2018)
In the work the effect of cryopreserved placental explants on the ovarian generative elements preservation after torsion treatment was defined. The ovarian torsion was modeled on the Wistar rats by the catgut ligation for 4 hours. It has been shown that the application of cryopreserved placental explants in combination with surgical treatment of experimental ovarian torsion allows to preserve part of the primordial follicles from death due to ischemic damage and restoring folliculogenesis. The uterus structure was restored independently of the therapy.
Keywords: ovarian torsion; placenta; cryopreservation; rats